2018
DOI: 10.1007/s00264-018-3787-0
|View full text |Cite|
|
Sign up to set email alerts
|

Regenerative therapies increase survivorship of avascular necrosis of the femoral head: a systematic review and meta-analysis

Abstract: Regenerative therapies offer good clinical results for the treatment of AVN. The combination of CD with regenerative techniques provides a significant improvement in terms of survivorship over time compared with CD alone. Further studies are needed to identify the best procedure and the most suitable patients to benefit from regenerative treatments for AVN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 67 publications
1
56
0
3
Order By: Relevance
“…Since then, pre-clinical studies and human studies employing unselected BM-derived cells, circulating angiogenic cells, and mesenchymal stem cells have shown that injection of those cells to the femoral head was able to ameliorate hip performance. Andriolo et al [38] confirm with a systematic review and meta-analysis that regenerative therapies increase survivorship of avascular necrosis of the femoral head, which is confirmed by Hernigou et al [39] who report a prospective, randomized trial investigating long-term effects of bone marrow cell therapy in patients with bilateral osteonecrosis.…”
Section: Cell Therapy and Osteonecrosismentioning
confidence: 72%
“…Since then, pre-clinical studies and human studies employing unselected BM-derived cells, circulating angiogenic cells, and mesenchymal stem cells have shown that injection of those cells to the femoral head was able to ameliorate hip performance. Andriolo et al [38] confirm with a systematic review and meta-analysis that regenerative therapies increase survivorship of avascular necrosis of the femoral head, which is confirmed by Hernigou et al [39] who report a prospective, randomized trial investigating long-term effects of bone marrow cell therapy in patients with bilateral osteonecrosis.…”
Section: Cell Therapy and Osteonecrosismentioning
confidence: 72%
“…In this study, no complication occurred during auto-PBSC mobilization, collection, and infusion, proving that it is a safe intervention for patients with ONFH. As PBSCs, theoretically, have the potential to differentiate into vascular endothelial cells and secrete biologically active paracrine factors for regeneration [14,15], this study cohort, exhibiting a 50 ± 7% hip-preservation success rate at 5-year follow-up, supports the efficacy of auto-PBSC transplantation for ONFH compared with previous studies, which suggested that > 50% of patients with ONFH required THA within 3 years of diagnosis [16,17]. However, the outcomes were individually different; therefore, the factors that led to this difference were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, it is challenging to determine how to prevent the progression of early-stage ONFH or to completely repair the necrotic areas to avoid THA. Core decompression is one of the available early treatments [4] and can significantly relieve pain in patients with early-stage ONFH [5]. However, a considerable number of patients do not achieve a satisfactory outcome in terms of repair of the femoral head necrotic area [5].…”
Section: Introductionmentioning
confidence: 99%
“…Core decompression is one of the available early treatments [4] and can significantly relieve pain in patients with early-stage ONFH [5]. However, a considerable number of patients do not achieve a satisfactory outcome in terms of repair of the femoral head necrotic area [5]. Femoral head necrosis is a disease involving the activity of local stem cells in the femoral head [6].…”
Section: Introductionmentioning
confidence: 99%